Damage of polyesters by the atmospheric free radical oxidant NO3•: a product study involving model systems - Goeschen, Catrin; Wille, Uta (Beilstein Journal of Organic Chemistry, 2013)
Manufactured polymer materials are used in increasingly demanding applications, but their lifetime is strongly influenced by environmental conditions. In particular, weathering and ageing leads to dramatic changes in the properties of the polymers, which results in decreased service life and limited usage. Despite the heavy reliance of our society on polymers, the mechanism of their degradation upon exposure to environmental oxidants is barely understood. In this work, model systems of important structural motifs in commercial high-performing polyesters were used to study the reaction with the night-time free radical oxidant NO3• in the absence and presence of other radical and non-radical oxidants. Identification of the products revealed ‘hot spots’ in polyesters that are particularly vulnerable to attack by NO3• and insight into the mechanism of oxidative damage by this environmentally important radical. It is suggested that both intermediates as well as products of these reactions are potentially capable of promoting further degradation processes in polyesters under environmental conditions.
Keywords: environmental oxidants; free radicals; nitrate radicals; polyester degradation; product studies; reaction mechanisms

(untitled) - Bolland, J. L. (Proc. R. Soc. London, Ser. A, 1946)

(untitled) - Bolland, J. L.; Gee, G. (Trans. Faraday Soc., 1946)

(untitled) - Bolland, J. L.; ten Have, P. (Discuss. Faraday Soc., 1947)

(untitled) - Bateman, L. (Q. Rev., Chem. Soc., 1954)

(untitled) - Bolland, J. L.; Gee, G. (Trans. Faraday Soc., 1946)

(untitled) - Gryn’ova, G.; Hodgson, J. L.; Coote, M. L. (Org. Biomol. Chem., 2011)

(untitled) - Wayne, R. P.; Barnes, I.; Biggs, P.; Burrows, J. P.; Canosa-Mas, C. E.; Hjorth, J.; Le Bras, G.; Moortgat, G. K.; Perner, D.; Restelli, G.; Sidebottom, H. (Atmos. Environ., Part A, 1991)

The Nitrate Radical: Physics, Chemistry and the Atmosphere - Air Pollution Report 31 - Wayne, R. P.; Barnes, I.; Biggs, P.; Burrows, J. P.; Canosa-Mas, C. E.; Hjorth, J.; Le Bras, G.; Moortgat, G. K.; Perner, D.; Restelli, G.; Sidebottom, H. (CEC, 1991)

(untitled) - Neta, O.; Huie, R. E. (J. Phys. Chem., 1986)

(untitled) - Goeschen, C.; Wibowo, N.; White, J. M.; Wille, U. (Org. Biomol. Chem., 2011)

(untitled) - Sigmund, D. C. E.; Wille, U. (Chem. Commun., 2008)

(untitled) - Goeschen, C.; White, J. M.; Gable, R. W.; Wille, U. (Aust. J. Chem., 2012)

(untitled) - Wille, U.; Goeschen, C. (Aust. J. Chem., 2011)

(untitled) - Nair, V.; Deepthi, A. (Chem. Rev., 2007)

(untitled) - Redmond, T. F.; Wayland, B. B. (J. Phys. Chem., 1968)

(untitled) - Pfrang, C.; Martin, R. S.; Canosa-Mas, C. E.; Wayne, R. P. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Bak, R. R.; Smallridge, A. J. (Tetrahedron Lett., 2001)

(untitled) - Lindsay Smith, J. R.; Nagatomi, E.; Stead, A.; Waddington, D. J.; Bévière, S. D. (J. Chem. Soc., Perkin Trans. 2, 2000)

(untitled) - Lindsay Smith, J. R.; Nagatomi, E.; Waddington, D. J. (J. Chem. Soc., Perkin Trans. 2, 2000)

(untitled) - Lindsay Smith, J. R.; Nagatomi, E.; Stead, A.; Waddington, D. J. (J. Chem. Soc., Perkin Trans. 2, 2001)

Comprehensive Handbook of Chemical Bond Energies - Luo, Y. R. (CRC Press, 2007)

(untitled) - Ito, O.; Akiho, S.; Iino, M. (J. Org. Chem., 1989)

(untitled) - Del Giacco, T.; Baciocchi, E.; Steenken, S. (J. Phys. Chem., 1993)

(untitled) - Atkinson, R. (J. Phys. Chem. Ref. Data, 1991)

N-Centered Radicals - Wayne, R. P. (Experimental study of the nitrate radical, 1998)

(untitled) - Shono, T.; Yamamoto, Y.; Takigawa, K.; Maekawa, H.; Ishifune, M.; Kashimura, S. (Chem. Lett., 1994)

(untitled) - Wille, U. (J. Phys. Org. Chem., 2011)

(untitled) - Wille, U. (Chem. Rev., 2013)

(untitled) - D'Anna, B.; Andresen, Ø.; Gefen, Z.; Nielsen, C. J. (Phys. Chem. Chem. Phys., 2001)

(untitled) - Suzuki, H.; Mori, T. (J. Chem. Soc., Perkin Trans. 2, 1997)
And literature cited therein.

(untitled) - Shafirovich, V.; Cadet, J.; Gasparutto, D.; Dourandin, A.; Geacintov, N. E. (Chem. Res. Toxicol., 2001)

(untitled) - Takami, M.; Matsuura, T.; Saito, I. (Tetrahedron Lett., 1974)

(untitled) - Petersen, W. C.; Letsinger, R. L. (Tetrahedron Lett., 1971)